Penguatan Profil Pelajar Pancasila Melalui Kegiatan Keagamaan di SMA Negeri Mojogedang Kabupaten Karanganyar - Rochmawan, Alfian Eko; Abbas, Ngatmin; Ulfah, Yetty Faridatul; Nashir, Muhammad Ja'far; Nashihin, Husna (Research and Social Study Institute, 2024)
This community service aims to illustrate the implementation of Community Service (PKM) between Mamba'ul 'Ulum Islamic Institute Surakarta and Mojogedang Public High School, Karanganyar Regency. The main focus is on strengthening the Pancasila student profile through religious activities, particularly the celebration of the Prophet Muhammad's birthday, held on Friday, October 6, 2023. The community service method involves the active participation of students in various spiritual, academic, and social activities. The results indicate that the integration of religious values with Pancasila can shape students with balanced and integral characters. This community service provides a positive contribution to the students' development and strengthens the bond between educational institutions and the community.